Early and Midterm Outcomes of Percutaneous Arteriovenous Fistula Creation - Ahmed Kamel Abdel Aal; Juri Bassuner; Husameddin El Khudari; Reema F. Alrasheed; Shahroz Aziz; Mohamed Shahin; Ammar Almehmi; Bridget Kowalczyk (The Arab Journal of Interventional Radiology)
Surgical creation of arteriovenous fistulas has been the gold standard for vascular access in hemodialysis patients. However, recent advancements in endovascular technology, the need for alternative hemodialysis access options in nonsurgical candidates, and patient preference for nonsurgical approaches have led to the development of percutaneous arteriovenous fistula creation. Currently, there are two Food and Drug Administration (FDA) approved systems, namely WavelinQ and Ellipsys. The aim of this article is to review the available literature on the outcomes of percutaneous arteriovenous fistula creation. Studies have reported high technical success rates for both the WavelinQ and Ellipsys systems. However, re-interventions were necessary for maturation, maintenance of patency, and treatment of complications. Reported re-intervention rates have varied across studies, device used, and patient populations, ranging from 0.46 to 2.7 per patient-year. While percutaneous arteriovenous fistula creation shows promise in terms of technical success rates, patency, and patient satisfaction, the rate of re-interventions adds to the overall procedural burden and may impact cost-effectiveness.